A CENTRAL ROLE FOR INDUCIBLE HEAT SHOCK PROTEIN 70 IN AUTOIMMUNE VITILIGO - Mosenson, Jeffrey A. (2013)
Inducible Heat Shock Protein 70 (HSP70i) is a protein regulated by stress that protects cells from undergoing apoptosis. Such proteins are marvelously well conserved throughout evolution, which has placed them in the spotlight for helping to understand the intriguing relationship between infection and immunity. In the presence of stress proteins, dendritic cells (DCs) will sense this alarm signal and respond by recruiting immune cells of different plumage to fit the occasion. In times of stress, melanocytes will secrete antigen bound HSP70i to act as an alarm signal in activating DCs, that comes equipped with an address of origin to drive the autoimmune response in vitiligo. Here we pose that if the autoimmune response is funneled through HSP70i, then blocking the stress protein from activating DCs can lend new treatment opportunities for vitiligo.